Newcomers’ organizational socialization: the role of co-worker support, organizational support and proactive behaviour - James, R. (Journal of Business Studies, 2020)
The recent studies found that newcomers’self-initiated activates are the significant predictor of newcomers' adjustment and organizational socialization. Also, organizational socialization scholars propose that newcomers' self-initiated activates may be more critical than the traditional approach to organizational socialization. Therefore, there is a need to identify whether the traditional approach (support practices) or newcomers' self-initiated activates (proactive behaviour) play a significant role in the socialization process. Therefore this study aims to identify the relative importance of support practices and newcomers' proactive behaviour during the socialization. This study also investigates the role of support practices in newcomers' engagement in proactive behaviour and the influence of proactive behaviour on the relationship between support practices and newcomers' socialization. The study was conducted with 104 newcomers from diverse business organizations. PLS-SEM was employed to assess the proposed model. The results indicated that the higher the level of organizational support and co-worker support higher the level of newcomers' engagement in proactive behaviour and the higher the level of proactive engagement and co-worker support the higher the level of newcomers' socialization. Further, this study found that newcomers' engagement in proactive behaviour mediates the relationship between newcomers' perceived support practices and socialization. The findings of this study deepen the understanding of the socialization process and help the management and the newcomers recognize their role in the successful socialization process.
Keywords: Co-worker; support organizational support; Proactive behaviour; Socialization; Resources; Role transition